Biofortification: Future challenges for a newly emerging technology to improve nutrition security sustainably - Bouis, Howarth E.; Foley, Jennifer; Lividini, Keith; Jumrani, Jaya; Reinke, Russell; Van Der Straeten, Dominique; Zagado, Ronan; Boy, Erick; Brown, Lynn R.; Mudyahoto, Bho; Alioma, Richard; Hussain, Munawar; et al. (Elsevier, 2024)
Biofortification was coined as a term to define a plant breeding strategy to increase the micronutrient content of staple food crops to reduce the burden of micronutrient deficiencies in low- and middle-income countries (LMICs). In 2003, the HarvestPlus program, based in the centers comprising the Consultative Group on International Agricultural Research (CGIAR), was initiated to implement the biofortification strategy. This paper discusses what has been achieved, what has been learned, and the key challenges to embed biofortification in food systems and to expand its impact.